Firm performance: HR practices and IT - Kengatharan, N. (My University, 2020)
Information technology is an integral part of organisational life, spilling over into operational functions of the organisations. Anchored in the resource-based theory of the firm and the Ability-Motivation-Opportunity theory, the study aims to investigate the direct and combined effects of human resource management practices and information technology on firm performance. Data were garnered from 147 financial and non-financial firm managers using a convenience sampling technique, with a self-administrated questionnaire. As a caveat, reliability and validity of the measures, and common method variance were examined. The results confirms that human resource management practices significantly contribute to firm performance . The combined effect of human resource management practices with information technology has significantly positively related to firm performance such the positive relationship between human resource management practices and firm performance is stronger at a high usage of technology than at low usage.
Keywords: Human resource management practices; Firm performance; Information technology; Ability- Motivation-Opportunity theory